Predictors of successful endovascular treatment in severe cerebral venous sinus thrombosis - Yang, Xiaoxu (Ann Clin Transl Neurol, 2019)
OBJECTIVE: The objective of this study was to evaluate the thrombus characteristics affecting the extent of recanalization to identify patients with severe cerebral venous sinus thrombus (CVT) more likely to benefit from endovascular therapy. METHODS: Severe CVT patients scheduled for endovascular treatment were prospectively recruited into the study. Each thrombosed venous segment was evaluated regarding complete or partial recanalization based on digital subtraction angiography (DSA) after treatment. Magnetic resonance black‐blood thrombus imaging (MRBTI) was performed 1 day before endovascular treatment. The signal‐to‐noise ratio (SNR) of the clot, age of the clot, and baseline volume of the clot were compared between the complete and partial recanalization groups. A logistic regression analysis was performed to identify the association between these clot characteristics and recanalization status. RESULTS: Twenty‐one CVT patients undergoing endovascular therapy were prospectively included. There were 110 thrombosed segments, 54 of these segments were completely recanalized after endovascular treatment. An acute clot sign (ACS) was found in 39 segments and a subacute clot sign (SCS) was found in 71 segments. There was no significant difference on baseline volume of the clot (1638.8 ± 1432.2 mm(3) vs. 1957.5 ± 2056.1 mm(3), P > 0.05) between the complete and partial recanalization groups. Logistic regression analysis showed that ACS on MRBTI was associated with complete recanalization (P < 0.001, odds ratio = 3.937, 95% confidence interval, 1.6–9.5). INTERPRETATION: ACS can be used to predict complete recanalization in patients undergoing endovascular treatment. MRBTI provides a robust method to define clot composition and is potentially useful in selecting the most appropriate CVT patients for endovascular treatment.